Proterozoic–Paleozoic Sedimentary Rocks and Mesozoic–Cenozoic Landscapes of the Cape Mountains Across the Kango Complex Reveal ‘More Gaps Than Record’ from Rodinia and Gondwana to Africa - de Wit, Maarten J.; Linol, Bastien; Nengovhela, Vhuhwavhohau (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2020)
The Kango (Cango) region flanks the northern margins of the Klein Karoo and the Cape Mountains across the Western Cape Province of South Africa. It preserves a condensed Proterozoic–Paleozoic stratigraphy exposed via a Mesozoic–Cenozoic morphology with a present Alpine-like topography. Its rocks and landscapes have been repeatedly mapped and documented for the past 150 years. Over the last 25 years, we remapped and dated a central-eastern section of this region. The subvertically bedded and cleaved rocks reveal an 8–10 km thick stratigraphy covering more than 700 million years between ca. 1200 and 500 Ma with several unconformities and disconformities. At ca. 252 Ma, during the Cape orogeny, this Kango Complex was deformed along thrusts and sub-isoclinal folds producing steeply dipping phyllites and slates. It was uplifted by 3–5 km during the Kalahari epeirogeny between 140 and 60 Ma while eroding at ca. 100–200 m/m.y. (120–80 Ma). During the Cenozoic, the rate of uplift decreased by an order of magnitude and today is ca. 0.4–0.7 m/m.y. across steep slopes and canyons in contrast to the Himalayas where erosion rates are about hundred times faster. A recent publication about this central-eastern section of the Kango region disputes the existence of regional isoclinal folds and suggests that deposition of the oldest sedimentary successions, including carbonate rocks of the Cango Caves (limestone-marble with enigmatic microfossils) was simple, continuous and restricted to between ca. 700 and 500 Ma, decreasing earlier estimates of the stratigraphic age range by 60–80%. Similarly, recent interpretations of the complex landscapes link the northern contact between the Kango and Table Mountain rock sequences to Quaternary faults. We present a new geological database, mapped between 1:500 and 1:10,000 scales, and twelve stratigraphic sections with younging directions linked to structural and isotopic data that support repetitions along regional isoclinal folds and thrust zones of the Kango sequences during the Permo–Triassic Cape orogeny, and geomorphic data that link the origin of its landscapes to weathering and erosion during the Cretaceous–Cenozoic Kalahari epeirogeny. During its evolution, the Kango Basin directly flanked both Grenvillian and Pan-African Mountain systems. But, at an average sedimentation rate of ca. 1 mm/70 years (0.014 mm/year) and with present low erosion rates (0.005 mm/year), there is likely more time missing than preserved of the tectono-erosion across these different regions of Rodinia and Gondwana before Africa emerged. To further evaluate the geodynamic significance of these time gaps requires more field mapping linked to new transdisciplinary geosciences.